How evidence from observing attending physicians links to a competency‐based framework. Issue 6 (30th March 2017) - Bacchus, Maria; Ward, David R; de Grood, Jill; Lemaire, Jane B
Abstract : Context: Competency‐based medical education frameworks are often founded on a combination of existing research, educational principles and expert consensus. Our objective was to examine how components of the attending physician role, as determined by observing preceptors during their real‐world work, link to the CanMEDS Physician Competency Framework. Methods: This is a sub‐study of a broader study exploring the role of the attending physician by observing these doctors during their working day. The parent study revealed three overarching elements of the role that emerged from 14 themes and 123 sub‐themes: (i) Competence, defined as the execution of traditional physician competencies; (ii) Context, defined as the environment in which the role is carried out, and (iii) Conduct, defined as the manner of acting, or behaviours and attitudes in the role that helped to negotiate the complex environment. In this sub‐study, each sub‐theme, or 'role‐related component', was mapped to the competencies described in the CanMEDS 2005 and 2015 frameworks. Results: Many role‐related components from the Competence element were represented in the 2015 CanMEDS framework. No role‐related components from the Context element were represented. Some role‐related components from the Conduct element were represented. These Conduct role‐related components were better represented in the 2015 CanMEDS framework than in the 2005 framework. Conclusions: This study shows how the real‐world work of attending physicians links to the CanMEDS framework and provides empirical data identifying disconnects between espoused and observed behaviours. There is a conceptual gap where the contextual influences of physicians' work and the competencies required to adjust to these influences are missing from the framework. These concepts should be incorporated into learning both broadly, such as through an emphasis on context within curriculum development for the workplace (e.g. entrustable professional activities), and explicitly, through the introduction of novel competencies (e.g. the Conduct role‐related components described in this study).